Frontal affinity chromatography: An excellent method of analyzing weak biomolecular interactions based on a unique principle - Kasai, Kenichi (Biochimica et biophysica acta. General subjects, 2021)
Not only strong biomolecular interactions but also weak interactions play important roles in ensuring appropriate operations of many biological systems. Although a thorough investigation of the latter is essential in understanding life science, few suitable research tools are available because of inherent difficulties. Frontal affinity chromatography (FAC) is a versatile method that overcomes the inherent difficulties to provide accurate information on weak interactions. Since its concept and merit are not widely recognized, a comprehensive interpretation of FAC is provided in this review to encourage its application among researchers. FAC is based on a unique principle of measuring the binding strength by the delayed migration of an analyte through an affinity column. Its utility was elucidated via the lectin-glycan interactions. FAC has a great potential as a research tool to solve many difficult problems in general bioscience that are relevant to almost all researchers. •Frontal affinity chromatography; a powerful analytical tool for weak interactions.•Retardation analysis of molecular interaction based on a unique principle.•One of the most powerful tools for glycobiology, especially in lectin field.